2020
DOI: 10.1007/s00586-020-06478-5
|View full text |Cite
|
Sign up to set email alerts
|

Is there an optimal timing between radiotherapy and surgery to reduce wound complications in metastatic spine disease? A systematic review

Abstract: Purpose Surgery with radiation therapy (RT) is more effective in treating spinal metastases, than RT alone. However, RT when administered in close proximity to surgery may predispose to wound complications. There exist limited guidelines on the optimal timing between RT and surgery. The purpose of this systematic review is to: (1) address whether pre-operative RT (preop-RT) and/or post-operative RT (postop-RT) is associated with wound complications and (2) define the safe interval between RT and surgery or vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 75 publications
(109 reference statements)
0
17
0
Order By: Relevance
“…A recently published systemic review also advocated for 2 weeks (with a minimum of 7 days) between surgery and radiotherapy [ 50 ]. When the rates of wound complications were compared between SRS and conventional radiotherapy, many studies reported reduced wound complications in SRS patients [ 51 - 53 ].…”
Section: Radiotherapy For Metastatic Spinal Tumorsmentioning
confidence: 99%
“…A recently published systemic review also advocated for 2 weeks (with a minimum of 7 days) between surgery and radiotherapy [ 50 ]. When the rates of wound complications were compared between SRS and conventional radiotherapy, many studies reported reduced wound complications in SRS patients [ 51 - 53 ].…”
Section: Radiotherapy For Metastatic Spinal Tumorsmentioning
confidence: 99%
“…51 As alluded to by the aforementioned survey, there is no high-quality evidence on what radiotherapy time frame provides the best LC while minimizing results. Yet, based on a recent review of level III/IV data in the spinal metastasis population, 2 weeks postoperatively may be an ideal time point, 53 in line with the results of the Dea et al survey. 51 Additionally, using smaller fractions may help reduce skin toxicities, a finding that the Hyogo group 39 cited as a primary reason for shifting from fractions of 4.4 to 2.2 RBE.…”
Section: Radiation Planningmentioning
confidence: 76%
“…12 These skin toxicities are likely of increased importance in postoperative patients, as irradiation is a known risk factor for wound infection in spine oncology patients. 53 However, given that some recent evidence suggests that radiation may more strongly dictate LC than surgical margins, 9 many spinal oncologists recommend its use. 51 As alluded to by the aforementioned survey, there is no high-quality evidence on what radiotherapy time frame provides the best LC while minimizing results.…”
Section: Radiation Planningmentioning
confidence: 99%
“…After spinal surgery, patients were usually given a duration of at least 2 weeks to allow optimal wound healing before commencement of RT. 21 All patients underwent CT-based treatment planning. The target vertebral segments were identified using CT, MRI or PSMA-PET diagnostic imaging where available.…”
Section: Radiation Therapy Detailsmentioning
confidence: 99%